2023
DOI: 10.3390/life13081731
|View full text |Cite
|
Sign up to set email alerts
|

Novel Pharmacological Targets of Post-Traumatic Stress Disorders

Abstract: Post-traumatic stress disorder (PTSD) is a psychopathological condition with a heterogeneous clinical picture that is complex and challenging to treat. Its multifaceted pathophysiology still remains an unresolved question and certainly contributes to this issue. The pharmacological treatment of PTSD is mainly empirical and centered on the serotonergic system. Since the therapeutic response to prescribed drugs targeting single symptoms is generally inconsistent, there is an urgent need for novel pathogenetic hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 135 publications
(156 reference statements)
0
1
0
Order By: Relevance
“…Preclinical studies on anxiety-related disorders in rodent models, characterized by abnormally persistent fear memories, such as PTSD and phobias, showed that CBD treatment could provide relief from symptoms [ 62 ]. Thus, the use of CBD and other medicinal cannabinoids has drawn increasing interest as a possible treatment strategy for the improvement of overall PTSD symptomatology as well as specific symptom domains, including sleep disorders, arousal disturbances and suicidal thoughts, also influencing quality of life, pain and social impact [ 63 ].…”
Section: Cb2r As a Potential Modulator Of Neuroinflammation And Neuro...mentioning
confidence: 99%
“…Preclinical studies on anxiety-related disorders in rodent models, characterized by abnormally persistent fear memories, such as PTSD and phobias, showed that CBD treatment could provide relief from symptoms [ 62 ]. Thus, the use of CBD and other medicinal cannabinoids has drawn increasing interest as a possible treatment strategy for the improvement of overall PTSD symptomatology as well as specific symptom domains, including sleep disorders, arousal disturbances and suicidal thoughts, also influencing quality of life, pain and social impact [ 63 ].…”
Section: Cb2r As a Potential Modulator Of Neuroinflammation And Neuro...mentioning
confidence: 99%